How to Predict the Vibration Energy Dissipation of Bolted Joint? - Lancereau, Damien (Cranfield University, 2017)
3MT presented at the 2017 Defence and Security Doctoral Symposium.The objective of this PhD is to investigate and understand the dynamics of joints in built-up structures. Currently, we do not understand the influence of the joints on the damping or the stiffness of a system. Our work will try to improve the quality of dynamics in finite element simulations. The aeronautic industry is currently limited in there design by the lake of dynamic joint model. For example, a problematic joint on the wing of the new Airbus A380 cost around one billion pounds to the company. Our approach is to start by focusing on experiments. We excite a structure and measure the response. Currently, we are investigating a two layer sandwich beams connected by bolts, which is already complex. The main challenge is the nonlinearity of built-up structures. To understand it, we decompose the response signal into different resonance modes, and then we fit short intervals of the signal to a mathematical model. This method gives time varying parameters which are simple to interpret. For example, a measurement of the size of a contact patch has been obtained from the shift in natural frequency. Also, measurements of the damping when correlated with measurements using a pressure film provided an insight of the position of the micro-friction interfaces in the system. And the use of shims in the interfaces allowed a better understanding of the interface.
Keywords: 'Vibration'; 'Dynamic'; 'Joint'; 'DSDS17 3MT'; 'DSDS17'; 'Dynamics; Vibration and Vibration Control'